Distributed Meetings: A Meeting Capture and Broadcasting System - Cutler, Ross; Rui, Yong; Gupta, Anoop; Cadiz, JJ; Tashev, Ivan; He, Li-wei; Colburn, Alex; Zhang, Zhengyou; Liu, Zicheng; Silverberg, Steve (Proceedings of ACM Multimedia 2002, 2002)
The common meeting is an integral part of everyday life for most workgroups. However, due to travel, time, or other constraints, people are often not able to attend all the meetings they need to. Teleconferencing and recording of meetings can address this problem. In this paper we describe a system that provides these features, as well as a user study evaluation of the system. The system uses a variety of capture devices (a novel 360º camera, a whiteboard camera, an overview camera, and a microphone array) to provide a rich experience for people who want to participate in a meeting from a distance. The system is also combined with speaker clustering, spatial indexing, and time compression to provide a rich experience for people who miss a meeting and want to watch it afterward.